Clinical outcomes for larynx patients with cancer treated with refinement of high‐dose radiation treatment volumes. Issue 8 (14th February 2020) - Burr, Adam R.; Harari, Paul M.; Haasl, Alyx M.; Wieland, Aaron M.; Bruce, Justine Y.; Kimple, Randall J.; Hartig, Gregory K.; McCulloch, Timothy M.; Witek, Matthew E.
Abstract: Background: To evaluate disease control, toxicities, and dose to dysphagia/aspiration risk structures (DARS) using a direct gross tumor volume (GTV70Gy ) to planning target volume expansion (dPTV70Gy ) for patients with squamous cell carcinoma of the larynx (LSCC). Methods: A retrospective review was performed on patients with LSCC treated between 2003 and 2018. Clinical outcomes, toxicities, and dosimetric data were analyzed. Results: Seventy‐three patients were identified. Overall survival at 5‐years was 57.8%. Five‐year local and regional control was 79.8% and 88.2%, respectively. Distant metastatic‐only failure was 2.7%. Eighty percent of failures were 95% contained within the dPTV70Gy . Mean dose and the volume of DARS receiving 70 Gy was significantly lower for dPTV70Gy compared to a consensus‐defined PTV70Gy . Discussion: Judicious reduction in high‐dose target volumes can preserve high tumor control rates while reducing dose to normal surrounding structures underscoring the potential benefit of this approach in enabling local therapy intensification to improve locoregional control.